Tribhuvan University certificate nursing curriculum - Regmi, K.; Regmi, S; Shahi, M. (Journal of Institute of Medicine Nepal, 2010)
Introduction: A Nepalese certificate of nursing curriculum was developed in 1977 and has been used since with a few revisions. There has been open debate about continuing gaps between theory, as expressed in the curriculum, and practice. The purpose of this study was to evaluate this 3-year undergraduate curriculum, and to draw general lessons, which might help to develop appropriate strategies to improve nursing education in Nepal. Methods: A mixed evaluation method was used consisting of reviews of current curriculum theories/ models, and interviews with nursing students (15) and nursing tutors (10). Results: Both students and tutors were generally positive about the curriculum and its intended learning outcomes. While reviewing the existing curriculum, analysis revealed that there was limited use of curriculum theories and models. Conclusions: There is a need to focus more on the development of abilities related to evidence-based learning. Selection of appropriate teaching-learning methodologies in response to the growing needs of students and professionals, development of learning strategies to reduce the gap between educational theories and nursing practice, in line with a humanistic paradigm in nursing education is important. Keywords: Curriculum evaluation, Nepal, nurses, nursing education. DOI: 10.3126/joim.v31i3.2997 Journal of Institute of Medicine, December, 2009; 31(3) 46-55